Green Marketing and Consumer Environmental Awareness: A Bibliometric Review of Social Education and Campaigns - Loso Judijanto; Ni Nyoman Suarniki; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This study employs bibliometric analysis to explore the expansive landscape of green marketing and consumer environmental awareness research. Utilizing data from VOSviewer, we analyzed thematic clusters, research trends, emerging topics, and author collaboration networks from a comprehensive dataset spanning several decades. Our findings reveal distinct thematic areas, including core marketing strategies, consumer behavior, corporate responsibility, and the critical evaluation of greenwashing practices. A temporal analysis indicates a shift in focus from traditional marketing tactics to nuanced understandings of consumer attitudes and the authenticity of environmental claims. Additionally, we identified potential research opportunities in underexplored areas such as green hotels and green markets, which could provide new insights into sector-specific sustainability practices. The author collaboration network analysis highlights a somewhat segmented academic community with opportunities for more interdisciplinary and integrative research efforts. This study not only charts the evolution and current state of green marketing research but also points to future directions that could bridge existing gaps and foster broader collaborative networks.